Enhanced Energy Conversion of Z907-Based Solar Cells by Cucurbit[7]uril Macrocycles - Al-Dmour, Hmoud; Alzard, Reem H.; Alblooshi, Hamda; Alhosani, Khaula; AlMadhoob, Shaqra; Saleh, Na'il (Frontiers in Chemistry, 2019)
A dye-sensitized solar cell was constructed on the basis of encapsulating the ruthenium polypyridyl photosensitizer Z907 in the macrocycle cucurbit[7]uril (CB7). The work focuses on the photophysical properties of the new host-guest complexes in acetonitrile and water (volume ratio 1:9) and on the top of nanocrystalline titanium dioxide (TiO2) electrode prior to the addition of poly(3-hexylthiophene) polymer and gold electrode. Complexation to CB7 in aqueous solutions has decreased the emission intensity and excited-state lifetime for metal-to ligand charge transfer (MLCT) state at 650 nm by 2-fold because of collisional quenching, which opens a non-radiative deactivation channel. Similarly, 2-fold decrease in the emission intensity and excited-state lifetime of MLCT at 750 nm on the top of TiO2 electrodes were observed with the addition of CB7. Encapsulation of Z907 dye to CB7 host has, also, led to 4-fold enhancement in the short circuit current and power conversion efficiency of the final solar cell. The results support the premise that host-guest complexation of CB7 facilities faster electron injection from Z907 dye into the conduction band of TiO2 electrodes.